1975
DOI: 10.1136/gut.16.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption in normal subjects and patients with idiopathic haemochromatosis: relationship with serum ferritin concentration.

Abstract: SUMMARY In 52 normal subjects there was an inverse relationship between serum ferritin concentration and iron absorption. In 21 measurements in 15 patients with idiopathic haemochromatosis there was a similar inverse relationship but absorption was higher in relation to iron stores at all levels. Haemochromatotic patients with normal serum ferritin levels had abnormally high values for desferrioxamine chelatable iron and there was no correlation between chelatable iron and iron absorption.Iron balance is maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 18 publications
1
32
0
2
Order By: Relevance
“…Thus, in our study there was greater likelihood of inhibition of iron absorption by mixing of the dose with formula or formula components in the stomach or upper small intestine. Studies of adult subjects given oral doses of radioisotopes of iron under standardized, fasting conditions have demonstrated a significant inverse relationship between percentage of the dose of 59Fe absorbed and serum femtin concentration (17)(18)(19)(20)(21)(22). As would be expected, the correlation is higher when the population studied includes both normal and iron-deficient subjects.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, in our study there was greater likelihood of inhibition of iron absorption by mixing of the dose with formula or formula components in the stomach or upper small intestine. Studies of adult subjects given oral doses of radioisotopes of iron under standardized, fasting conditions have demonstrated a significant inverse relationship between percentage of the dose of 59Fe absorbed and serum femtin concentration (17)(18)(19)(20)(21)(22). As would be expected, the correlation is higher when the population studied includes both normal and iron-deficient subjects.…”
mentioning
confidence: 60%
“…Even when the analysis is restricted to iron-suficient subjects, the correlation is significant. In iron-sufficient adult subjects, Walters et al (18) reported a correlation coefficient of -0.398 ( p < 0.005) for the regression of percent absorption on serum ferritin concentration and Heinrich et al (20) reported a correlation coefficient of -0.356 ( p < 0.01) for the regression of log serum femtin concentration on percent absorption. Neither Walters et al (1 8) nor Heinrich et al (20) calculated the regression on a sex-specific basis, although there was a significant sex-related difference in serum concentration of femtin among the subjects studied by Walters et al (18) and probably among the subjects studied by Heinrich et al (20).…”
mentioning
confidence: 99%
“…The central disturbance in IH is excessive absorption ofdietary iron despite expanded body iron stores (25)(26)(27). By simultaneously labeling the nonheme and heme iron compartments of the hamburger meal used in this study, it is possible to obtain quantitative estimates of total absorbed dietary iron.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to reduce or increase absorption of iron in response to increased or reduced iron stores is well documented. In HH, patients fail to decrease their iron absorption despite the accumulation of iron in the body (30)(31)(32).…”
Section: Failure To Regulate Iron Absorption In ~2m -/-Micementioning
confidence: 99%